2020
DOI: 10.3991/ijet.v15i12.14531
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Influential Factors of the Autonomous Learning Ability of Japanese Majors

Abstract: The autonomous learning of Japanese majors is affected by various factors and the learning effect is generally undesirable. To solve the problem, this paper aims to develop a model for the influencing factors of the autonomous learning of Japanese majors. Firstly, the authors explored the problems and influencing factors of autonomous learning of Japanese majors. On this basis, several suggestions were put forward to solve these problems. Next, gray system theory (GST) and analytical hierarchy process (AHP) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Particular consideration in scientific research is given to studying factors influencing the students' learning outcomes [32,33]. It is indicated that web-based and mobile autonomous learning, grounded in humanism and constructivism ideas, has combined self-directed training and Internet/mobile technology and opened up a new learning path [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particular consideration in scientific research is given to studying factors influencing the students' learning outcomes [32,33]. It is indicated that web-based and mobile autonomous learning, grounded in humanism and constructivism ideas, has combined self-directed training and Internet/mobile technology and opened up a new learning path [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of the flipped classroom, autonomous learning is promoted by providing students with the resources to investigate, discover, and understand concepts on their own (Li & Jin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Self-monitoring involves managing time and overcoming psychological barriers to achieve academic goals (Li & Jin, 2020), and self-assessment implies that the students value their own learning and work (Kambourova, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese majors need good Japanese language skills to complete business or communication works in the future. Now, the school teaching time in colleges and universities is not enough to make students proficient in another language, and in such case, autonomous learning becomes particularly important [7,8]. Some scholars have proposed that autonomous learning can be divided into forethought phase, performance phase, and self-reflection phase, which are determined by the individual, environment and behavior, respectively [9].…”
Section: Introductionmentioning
confidence: 99%